Body dissatisfaction, narcissism and self-esteem in young men and women: A moderated mediation analysis. (1st September 2018) - Purton, Terry; Officer, Charlotte; Bullivant, Bianca; Mitchison, Deborah; Griffiths, Scott; Murray, Stuart B.; Mond, Jonathan
Abstract: We sought to examine the associations between grandiose (GN) and vulnerable (VN) subtypes of narcissism and body dissatisfaction (BD), and moderation of these associations by sex, in young men and women, controlling for self-esteem (SE). Three hundred and fifty seven men and women aged 18 to 30 completed an online survey that included measures of GN, VN, BD, and SE. For both men and women, VN was positively correlated with BD and VN was negatively correlated with SE, while GN was (positively) correlated with SE only in women. Initial analysis suggested a role of SE in mediating the association between VN and BD. Moderated mediation analysis confirmed that the association between VN and BD was (fully) mediated by SE and that there was no moderation of this association by sex. The findings support the multidimensional nature of narcissism in young people and highlight the role of SE in accounting for the effects of VN on BD. Further research is needed to elucidate the direction of these associations and to consider their practical implications. Highlights: Vulnerable narcissism is positively associated with body dissatisfaction. Grandiose narcissism is not associated with body dissatisfaction. Self-esteem mediates the vulnerable narcissism-body dissatisfaction association. This association is not moderated by sex. Findings highlight the multidimensional nature of narcissism.